The global landscape of lean metabolic dysfunction-associated steatotic liver disease: insight from Asia and the West - Purnomo, Hery Djagat; Adiwinata, Randy; Permatadewi, Cecilia Oktaria; Hutami, Hesti Triwahyu; Indiarso, Didik (Frontiers in Gastroenterology, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD) has emerged as a leading global cause of chronic liver disease, affecting 25–30% of the population. While MASLD is traditionally associated with obesity, lean MASLD—a subset characterized by hepatic steatosis and metabolic dysfunction in individuals with a normal body mass index (BMI)—is increasingly recognized as a distinct clinical entity. Lean MASLD accounts for approximately 5.1% of the global population and is more prevalent in Asia, where genetic predispositions such as PNPLA3 and TM6SF2 polymorphisms, visceral obesity, and high-carbohydrate dietary patterns are key risk factors. Lean MASLD is also associated with significant liver and non-liver complications, as well as increased all-cause mortality risk. Therefore, lean MASLD may pose a significant challenge for practitioners.